Isometries of a function space - U. D. Vyas (International Journal of Mathematics and Mathematical Sciences)
It is proved here that an isometry on the subset of all positive functions of L1⋂Lp(ℝ) can be characterized by means of a function h together with a Borel measurable mapping ϕ of ℝ, thus generalizing the Banach-Lamparti theorem of Lp spaces.